Topical Issues of Improving the Activities of Police Commissions of the National Police of Ukraine - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied the current state of the regulatory base on the activities of police commissions, including the provisions of the Law of Ukraine "On the National Police", the Procedure for organizing the selection (competition) and promotion of police officers, as well as the Model procedure for holding a competition for police service and/or occupying a vacant positions.